Customers’ Preference of Mobile Phone Service Providers in Ekiti State, Nigeria - Niyi Israel, Akeke; Temitope Emmanuel, Akinruwa; Adenike Rita, Akeke (British Journal of Marketing Studies, 2016)
The objective of the study is to examine customers’ preference for mobile phone service providers in Ekiti State. Survey research designed was adopted while a self developed structured questionnaire was used to collect data. Data was analysed using multiple regression analysis through Statistical Package for Social Sciences (SPSS) version 20. The significance levels were tested at 5%. Findings show that connectivity was considered most significant with customers’ preference for mobile phone service providers in the state. Arising from finding, the study recommended that management of service providers should give more attention on improving their connectivity, relax their tariff rate and consistently scan the business environment to discover a particular marketing tool that gives desirable result. In ranking, the result shows that connectivity came first, followed by tariff rate and next was network coverage and finally quality of service.